Upaya Pencegahan Infiltrasi Pada Terapi Intravena Perifer di Rumah Sakit Awal Bros Batam: Infiltration Prevention Efforts in Peripheral Intravenous Therapy at Awal Bros Hospital Batam - Indah Purnama Sari; Hema Malini; Yulia Yasman (Fakultas Keperawatan Universitas Andalas, 2019)
Efforts to prevent infection, such as infiltration, is a critical aspect of the factors that affect the safety of patients. One form of safety for patients is the prevention of infiltration. An initial assessment tool was introduced to the nurses inward in order to ensure they performed the precaution behavior. The purpose of this study is knowing intravenous infiltration prevention efforts that have been done by nurses. The research method is descriptive observational, where research using total sampling inpatient nurses to observe the actions of nurses during infusion. There was 82 nurses the population and sampled by the researchers. The observation was conducted in the first week of patients' admission when many activities of intravenous therapy provided by nurses. The study found that nearly all the nurses were able to perform infiltration prevention activities during the infusion. It indicates that the nurse had been able to make active efforts in the prevention of infiltrates. These active efforts will continue to do so suggested the incidence of infiltration or due to the continued infusion of infection can be prevented.